Pengaruh Job Stress, Job Satisfaction, dan Organizational Commitment terhadap Turnover Intention pada Awak Kabin (Studi Kasus : PT XYZ) - Sutedjo, Yonas P.; Thjia, Martinus (Sam Ratulangi University, 2021)
This study aims to analyze several factors that can affect the occurrence of turnover in cabin crew that occurs at PT XYZ. The factors used in this study are job stress, job satisfaction, and organizational commitment. The target population used in this study is the cabin crew of PT XYZ, which resigned in 2015 – 2019 with a subject of 200 available data. The collection technique used in this study is to directly request the database of cabin crew who resigned from the XYZ human capital unit from 2015 – 2019, then create a sample frame from the data. In this study, the authors analyzed the data using the structural equation model. The results of the study indicate that job stress, lack of job satisfaction and lack of organizational commitment are the causes of turnover in the cabin crew of PT XYZ.